Critical reading for college and beyond - Daiek, Deborah B. (McGraw-Hill, 2004)
Critical Reading for College and Beyond uses regular journaling and self-assessment techniques to help students hone their abilities to read, analyze, and respond to textbooks and other college-appropriate materials